Ohněm a mečem a vždy s elegancí. O polemickém stylu jako homogenizačním prvku české a chorvatské moderny - Ivanković, Katica, bohemistica (Array, 2013)
With Fire and Sword, but Elegantly. On the Polemical Style as the Unifying Element of the Croatian and Czech Moderna In Czech and Croatian literature a traditional literary historical term Moderna mostly refers to the turn of the century literature. Besides the Czech and Croatian literary terminology, its use is limited to only few other countries of the Middle European region. The main characteristic of this period is a variety of literary trends and it is thus perceived as unhomogeneuos. Ever since the 1980s, the term Moderna has been an object of dispute and relativisation, which is partially due to the fact that it is intertwined with a seemingly related term Modernism. This article aims to discover the unifying element of the Middle European Moderna by exploring the extremely well developed literary criticism of the time. The most important representatives of the Czech and Croatian Moderna are the classics of literary criticism, F. X. Šalda and A.G. Matoš, who stand out due to the specific highly polemical style of their literary criticism.